STRATEGI PENGEMBANGAN KEBERLANJUTAN PANGAN (Kasus Komoditas Cabai Merah di Kabupaten Garut) - Aulia Rahmah; Mia Rosmiati; Angga Dwiartama (JURNAL AGRIBISNIS TERPADU, 2017)
Despite its broad and vague definition, sustainable development has become an ideal development paradigm for many countries around the world. Including Indonesia as one of the countries that also commit to realize sustainable development. Unfortunately, Indonesia's food development policy is still focused on food security. Developing sustainable food development in the world, added the concept of a strong food industry through growth and provision. This study aims to analyze and formulate alternative strategies in an effort to achieve sustainable development goals in the field of food, through a case example of chili in Garut regency. Primary data results through semi structured interviews, questionnaires, and observations of 27 key informants selected through snowball sampling techniques. Secondary data, obtained from various scientific media. Data were analyzed descriptively using sSWOT-QSPM. The results showed that the set of strategy (S-O, S-T, W-O, and W-T) yielded a score of attractiveness that was not much different. The strategic strategies that can be addressed and can be applied by stakeholders involved in the development of chili commodities are coordination of red chili cultivation schedule at the central location, increasing bargaining position of farmers, improving product quality, making information system price and weather / season, increasing intensity of educative activity of farmer.